Mapping the interconnectedness between EU banks and shadow banking entities - Jorge Abad; Marco D'Errico; Neill Killeen; Vera Luz; Tuomas A. Peltonen; Richard Portes; Teresa Urbano (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
This paper provides a unique snapshot of the exposures of EU banks to shadow banking entities within the global financial system. Drawing on a rich and novel dataset, the paper documents the cross-sector and cross-border linkages and considers which are the most relevant for systemic risk monitoring. From a macroprudential perspective, the identification of potential feedback and contagion channels arising from the linkages of banks and shadow banking entities is particularly challenging when shadow banking entities are domiciled in different jurisdictions. The analysis shows that many of the EU banks' exposures are towards non-EU entities, particularly US-domiciled shadow banking entities. At the individual level, banks' exposures are diversified although this diversification leads to high overlap across different types of shadow banking entities.
Keywords: F65; G21; G23; 330; shadow banking; interconnectedness; financial stability; macroprudential policy